1984
DOI: 10.1080/03014468400007241
|View full text |Cite
|
Sign up to set email alerts
|

New studies on the Macushi Indians of northern Brazil

Abstract: Demographic data and genetic information concerning 40 genetic systems are reported for three populations of Macushi Indians, and have been compared to those already obtained for three other communities of this tribe. These are young populations (mean age, 19 years), with a low sex ratio (90), low percentages of non-Indian ancestry (1-2%) and of marriages between locally born persons (34). Intertribal unions (14%) are less frequent than among their neighbours, the Wapishana. Fertility is high (average of 8.2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…On the negative side, the absence of commercially readily available antisera and the complexity of the typing procedures restrict its use. The presence of two concomitant nomenclatures and the varied number of re-Heavy chain localization Subclass Domain (3) tn Glm (17) (2) G2m (23) (n) G3m (5) (bl) G3m (6) (c3) G3m (10) (b5) G3m (11) (bO) G3m (13) (b3) G3m (14) (b4) G3m (15) ( 8 ) G3m (16) (t) G3m (21) (g1) G3m (24) (c5)…”
Section: North1mentioning
confidence: 99%
“…On the negative side, the absence of commercially readily available antisera and the complexity of the typing procedures restrict its use. The presence of two concomitant nomenclatures and the varied number of re-Heavy chain localization Subclass Domain (3) tn Glm (17) (2) G2m (23) (n) G3m (5) (bl) G3m (6) (c3) G3m (10) (b5) G3m (11) (bO) G3m (13) (b3) G3m (14) (b4) G3m (15) ( 8 ) G3m (16) (t) G3m (21) (g1) G3m (24) (c5)…”
Section: North1mentioning
confidence: 99%
“…The number of non-Indian subjects tested in South America (23,839) is about 40% higher than the total number of Indians (Table 2). There are now 13 variants that (1994); Krahó, 193, Neel (1978); Macushi, 694, Neel et al (1977), Salzano et al (1984); Mundurucu, 361, Salzano et al (1991), Santos et al (1998); Noanama, 155, Kirk et al (1974); Pacaá s Novos, 222, Salzano et al (1985b); Palikour, 115, Santos et al (1998); Parakanã , 252, Black et al (1980Black et al ( , 1988; Quechua, 39, Modiano et al (1972); Sateré-Mawé, 170, Salzano et al (1985a);Surui, 198, Callegari-Jacques et al (1994), Salzano et al (1998); Tenharim, 20, Santos et al (1998);Ticuna, 761, Neel et al (1980); Urubu-Kaapor, 205, Black et al (1988); Waiã pi, 361, Tchen et al (1978), Black et al (1983); Wai Wai, 166, Callegari-Jacques et al (1996); Zoró, 76, Salzano et al (1998 Tables 1 and 2 is more meaningful when considered in the context of the information provided in Tables 3 and 4. The provisional assignment of Belém 2 to albumin México by direct electrophoretic comparisons in four buffer systems is rendered plausible by previous studies in which the structural studies confirmed the electrophoretic findings (see Arai et al, 1989), as well as by the present results concerning albumin Fortaleza.…”
Section: Resultsmentioning
confidence: 99%
“…3 1:Arends et al (1969); 2:Santos et al (1998); 3:Arends et al (1970),Tanis et al (1973); 4: Neel (1978); 5:Salzano et al (1974b),Geerdink et al (1974); 6:Neel et al (1997),Salzano et al (1980b); 7:Salzano et al (1990); 8:Weitkamp et al (1973a),Salzano et al (1997b); 9:Ferrell et al (1978); 10: Populations for which no variants were found (name, sample size, and reference): Apalai-Wayana, 129,Salzano et al (1988), Arara, 61,Salzano et al (1991); Araucano (Mapuche), 314,Haas et al (1985),Carnese et al (1996),Goicoechea et al (1998); Araweté, 112,Salzano et al (1991); Asurini, 158,Black et al (1988); Aymará , 1379,Ferrell et al (1980); Ayoreo, 358,Salzano et al (1978); Baniwa, 377,Mohrenweiser et al (1979); Cayapo, 993, Salzano et al (1972), Callegari-Jacques et al (1994), Santos et al (1998); Central Pano, 463; Johnston et al (1969), Mohrenweiser et al (1979); Cinta Larga, 92, Callegari-Jacques et al (1994); Cofan, 68, Kirk et al (1974); Emerillon, 51, Tchen et al (1978); Gaviã o, 182, Salzano et al (1998); Guahibo (Cuiva), 104, Tchen et al (1979); Guarani, 80,Salzano et al (1997a); Içana Indians, 148,Salzano et al (1986); Ingano, 41,Kirk et al (1974); Jamamadi, 37,Salzano et al (1991); Kaingang, 449, Salzano et al (1980a, 1997a; Kanamari, 100,Mohrenweiser et al (1979); Karitiana, 94, Callegari-Jacques et al (1994); Krahó, 193, Neel (1978); Macushi, 694, Neel et al (1977),Salzano et al (1984); Mundurucu, 361,Salzano et al (1991),Santos et al (1998); Noanama, 155, Kirk et al (1974); Pacaá s Novos, 222, Salzano et al (1985b); Palikour, 115, Santos et al (1998); Parakanã , 252, Black et al (1980; Quechua, 39,Modiano et al (1972); Sateré- Mawé, 170, Salzano et al (1985a); Surui, 198, Callegari-Jacques et al (1994),Salzano et al (199...…”
mentioning
confidence: 99%
“…Information concerning the Gc isoelectrofocusing subtypes in Amerindians and related groups is increasing (Constans and Salzano, 1980;Matsumoto et al, 1980;Dykes et al, 1983;Szathmary et al, 1983;Salzano et al, 1984Salzano et al, , 1985present communication) and some first generalizations are now possible. In one Siberian population (Tuvintsi) the frequency of GclS (0.28) is lower than that of GcIF (0.52), but in two Eskimo and in 15 of 18 American Indian samples the opposite is true (frequency of GclS > frequency of Gc'~); the exceptions are the Pima of the United States and the Kraho and Pacaas Novos of Brazil.…”
Section: Discussionmentioning
confidence: 99%